Wnt/β-Catenin Pathway-Regulated Fibromodulin Expression Is Crucial for Breast Cancer Metastasis and Inhibited by Aspirin - Khan, Fahim Ullah; Owusu-Tieku, Nana Yaa Gyaama; Dai, Xiaoyong; Liu, Kewei; Wu, Yanping; Tsai, Hsiang-I; Chen, Hongbo; Sun, Chunhui; Huang, Laiqiang (Frontiers in Pharmacology, 2019)
ABSTRACT Emerging evidence suggests that fibromodulin (FMOD), an extracellular matrix protein, is associated with cancer, yet little is known about the regulation of FMOD expression and its role in cancer metastasis. Aspirin, a classic anti-inflammatory drug, has been indicated to offer anticancer benefits, but its action targets and mechanisms remain obscure. In the present study using cell lines, animal model and database analysis, we show that FMOD expression is regulated positively by Wnt/β-catenin pathway, wherein the β-catenin/TCF4/LEF1 complex binds FMOD promoter to transcribe FMOD which is essential for breast cancer cell migration and invasion (BCCMI) via activation of ERK. Aspirin inhibits BCCMI by suppressing Wnt/β-catenin signaling and hence FMOD expression via inhibiting HDAC6 deacetylation of β-catenin leading to β-catenin phosphorylation and degradation. Moreover, expression of β-catenin/TCF4/LEF1 complex components is upregulated by Wnt/β-catenin pathway, constituting positive feedback loops. Our findings identify a critical role of FMOD in cancer metastasis, reveal a mechanism regulating FMOD transcription and impacting tumor metastasis, uncover action targets and mechanism for the anticancer activity of Aspirin, and expand the understanding of Wnt/β-catenin pathway and tumor metastasis, which are valuable for development of cancer therapeutics.